Peran Baitul Maal Wat Tamwil (BMT) Husnayain Terhadap Perkembangan Usaha Mikro Kecil dan dan Menengah - Sumardi, Sumardi; Zulpahmi, Zulpahmi (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This study aims to determine the role of Baitul Maal Wat Tamwil (BMT) Husnayain Against the Development of Micro Small and Medium Enterprises (UMKM). In the study used survey methods by taking samples from the population. The sample in this research is Baitul Maal Wat Tamwil (BMT) Husnayain customer, with 65 respondents. Data processing techniques and data analysis used are validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test, and coefficient of determination. ttabel sebesar 1,998 dan signifikansi sebesar 0,004 < 0,05, sedangkan pembiayaan murabahah berpengaruh positif terhadap perkembangan usaha mikro">Based on the results of the discussion of al-qardhul al-hasan financing has a positive effect on the development of micro, small and medium enterprises small and medium with a tcount of 2,962> ttable of 1.998 and significance of 0.004 <0.05, while murabahah financing has a positive effect on the development of micro enterprises ttabel sebesar 1,998 dan signifikansi sebesar 0,046 < 0,05, dan pembiayaan mudharabah berpengaruh positif terhadap perkembangan usaha mikro, kecil dan menengah kecil dan menengah menunjukkan thitung sebesar 4,713 > ttabel sebesar 1,998 dan signifikansi">, Small and medium-sized small and medium enterprises shows t count of 2.195> ttable of 1.998 and significance of 0.046 <0.05, and mudharabah financing has a positive effect on the development of micro, small and medium enterprises small and medium scale shows tcount of 4.713> ttable of 1.998 and significance Ftabel 3,15 dan tingkat signifikansi sebesar 0,000 < 0,05 dengan demikian dapat dikatakan bahwa al-qardhul al-hasan, murabahah dan mudharabah secara bersama-sama berpengaruh signifikan terhadap perkembangan">0.000 <0.05, simultaneously that the value of Fcount 67,809> Ftable 3.15 and the significance level of 0.000 <0.05 thus it can be said that al-qardhul al-hasan, murabaha and mudaraba together significantly influence the development micro small and Medium Enterprises. Keywords; Financing of al-qardhul al-hasan; murabaha; mudaraba; and micro and small business (UMKM)